Cloning, expression and sequence analysis of a phenylalanine ammonia lyase gene BaPAL from Chinese kale (Brassica alboglabra) - JIANG Ming; LI Yan; CHEN Zhen; LI Jun-min; DU Zhao-kui (浙江大学学报. 农业与生命科学版)
Degenerate primers were designed according to known phenylalanine ammonia lyase (PAL) gene sequences of Arabidopsis thaliana, Brassica napus and Isatis indigotica. A gene, designated BaPAL, was isolated from leaf cDNA of Chinese kale (B. alboglabra). Sequence analysis showed that the coding sequence of BaPAL was 2 145 bp in length encoding 714 amino acids. BaPAL gene sequence was submitted to NCBI under the accession number FJ849059. Semi-quantitative RT-PCR was applied using roots, stems, leaves, flower buds, open flowers and siliquas cDNA as PCR templates, respectively. Results indicated that BaPAL gene was expressed in all organs with the exception of roots, and was highly expressed in open flowers. Sequence comparison of BaPAL and PALs from other plants revealed that B. alboglabra, B. napus and B. rapa var. Chinensis were the closest relatives. B. alboglabra had a closer relationship and shared the same clade in phylogenetic tree with I. indigotica and A. thaliana. However, it was distantly related to ferns for their low sequence homology.